2022
DOI: 10.3390/agriculture12091429
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-2 Data for Land Use Mapping: Comparing Different Supervised Classifications in Semi-Arid Areas

Abstract: Mapping and monitoring land use (LU) changes is one of the most effective ways to understand and manage land transformation. The main objectives of this study were to classify LU using supervised classification methods and to assess the effectiveness of various machine learning methods. The current investigation was conducted in the Nord-Est area of Tunisia, and an optical satellite image covering the study area was acquired from Sentinel-2. For LU mapping, we tested three machine learning models algorithms: R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…These improvements in classification accuracy for this study may be due to the use of vegetation indices and topographic factors as additional variables in refining the classification. In this regard, consistently with this study, a number of studies have shown the importance of vegetation indices and topographic factors in improving LULC classification accuracy [55,76,77].…”
Section: Lulc Classification and Change Detectionsupporting
confidence: 87%
See 1 more Smart Citation
“…These improvements in classification accuracy for this study may be due to the use of vegetation indices and topographic factors as additional variables in refining the classification. In this regard, consistently with this study, a number of studies have shown the importance of vegetation indices and topographic factors in improving LULC classification accuracy [55,76,77].…”
Section: Lulc Classification and Change Detectionsupporting
confidence: 87%
“…Among these variables, elevation was found to be the most important. Consistently with these findings, several studies have reported the importance of vegetation indices and topographic factors in improving LULC classification [55,76]. Among the vegetation indices, the NDVI was more important than the SAVI in most cases.…”
Section: Variable Importancesupporting
confidence: 68%
“…Similarly, the study observed confusion between the grassland and farmland. Mapping LULC with Sentinel-2 data in the semi-arid region is quite promising [34] but challenging because most crops are planted during the rainy season, and their growing season is in July and August, during which the cloud cover is high in the area. And the reliance on dry season imagery may not be feasible as there is a transition from cropland to barren land in the area, especially from early November.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial resolution of these data is 20 m. The data were pre-processed and atmospherically corrected by the providers. Sentinel-2 has promise in LULC mapping in semiarid/agriculturally dominant landscapes based on RF feature selection [33,34].…”
Section: Sentinel-2 Surface Reflectancementioning
confidence: 99%
“…According to Yang et al [19], the random forest (RF) [20] algorithm has been widely utilized in previous LULC studies [16,19,[21][22][23][24][25][26][27][28][29], followed by support vector machine (SVM) [30][31][32][33][34][35]. Li et al [36] conducted a comparison between the performance of the RF classification algorithm and other algorithms such as SVM and artificial neural network (ANN).…”
Section: Introductionmentioning
confidence: 99%